Utilization of near infrared reflectance spectroscopy for prediction of the nutritional composition of beef and pork samples - Lagombra, Gregorio Garcia; Harbers, L.H.; Velazco, J.; Morrill, J.L.; Maziya, B.B.; Harbers, C.A.Z. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Near-infrared reflectance spectroscopy (NIRS) offers the potential for rapid, low-cost analyses of meat samples. Beef and pork samples were analyzed by both standard laboratory (AOAC) methods and NIRS. Regression equations were developed to relate the two methods. Coefficients of determination between NIRS and AOAC results were .929 for dry matter, .965 for crude protein, and .996 for ether extract. NIRS and AOAC procedures yielded very similar results (DM, 38.82 vs 38.58; CP, 17.78 vs. 17.83; and EE, 18.83 vs. 18.00). NIRS appears to be a rapid and reliable predictor of nutritional composition of ground beef and pork based on regression equations we have developed with a limited number of samples.
Keywords: Beef; Near infrared reflectance spectroscopy; Pork/beef equations